Early wound complications after orthopaedic surgery for haemophilia: What can we do more. Issue 5 (1st August 2020) - Feng, Bin; Li, Zeng; Feng, Cheng; Zeng, Ang; Gao, Peng; Liu, Yong; Weng, Xisheng
Abstract: Background: The characteristics of the haemophilia may endanger the patient with haemophilia (PWH) to higher ratio of wound complication, even lead to the refractory wound problem. The early wound complication in PWH has not been well studied in literature. Methods: Between the period from 2002 to 2018, 250 patients underwent 323 elective orthopaedic surgical procedures for the treatment of haemophilic musculoskeletal disorders. The medical records were retrospectively reviewed. The patients were evaluated for postoperative wound complications within 30 days. Risk factors related to wound complications were further analysed. The patients underwent vacuum sealing drainage (VSD) for refractory wound healing problem were further analysed. Results: Twenty‐four patients of 250 patients experienced early wound complication within postoperative 30 days. The incidence of wound complication in the patients without preoperative infection was 6.5%. Positive inhibitor and surgery for pseudotumour were associated with higher rate of wound complication after logistic regression, with the odds ratios (OR) of 5.7 (95% CI, 1.08 to 30.3) and 4.9 (95% CI, 1.3 to 18.5), respectively. Eight patients underwent VSD treatment for refractory wound healing problem and recovered uneventfully. The total VSD treatment cycle was 2.25 (from 2 to 4). The average factor consumption was 26.1 IU kg −1  d −1 . The patients complicated with infection had higher, but not statistically significantly, treatment duration, factor consumption and peri‐VSD total blood loss than the patients without infection. Conclusions: PWH had an incidence of 6.5% of early wound healing problem after elective orthopaedic surgery for musculoskeletal disorder in the present study. The presence of positive inhibitor and surgical procedure for haemophiliac pseudotumour are associated with higher incidence of wound healing problem. The VSD is an effective alternative for the treatment of refractory wound healing problem for PWH, especially for the patients complicated with infection.